17.6%‐Efficient Quasiplanar Heterojunction Organic Solar Cells from a Chlorinated 3D Network Acceptor. Issue 37 (28th July 2021) - Chen, Hui; Zhao, Tingxing; Li, Long; Tan, Pu; Lai, Hanjian; Zhu, Yulin; Lai, Xue; Han, Liang; Zheng, Nan; Guo, Liang; He, Feng
Abstract: Bulk heterojunction (BHJ) organic solar cells (OSCs) have achieved great success because they overcome the shortcomings of short exciton diffusion distances. With the progress in material innovation and device technology, the efficiency of BHJ devices is continually being improved. For some special photovoltaic material systems, it is difficult to manipulate the miscibility and morphology of blend films, and this results in moderate, even poor device performance. Quasiplanar heterojunction (Q‐PHJ) OSCs have been proposed to exploit the excellent photovoltaic properties of these materials. An OSC with BTIC‐BO‐4Cl has a 3D interpenetrating network structure with multiple channels that can facilitate the exciton diffusion and charge transport, and BTIC‐BO‐4Cl is therefore a good candidate for Q‐PHJ OSCs. In this work, a D18:BTIC‐BO‐4Cl‐based Q‐PHJ device is fabricated. The exciton diffusion lengths of D18 and BTIC‐BO‐4Cl are in accord with the requirements of the Q‐PHJ device and the efficiency of Q‐PHJ device is as high as 17.60%. This study indicates that the Q‐PHJ architecture can replace the BHJ architecture to produce excellent OSCs for certain unique donors and acceptors, providing an alternative approach to photovoltaic material design and device fabrication. Abstract : Quasiplanar heterojunction (Q‐PHJ) organic solar cells (OSCs) based on D18 and BTIC‐BO‐4Cl with a 3D network are reported, yielding a high power conversion efficiency (PCE) of 17.60%. The results show that the Q‐PHJ architecture can replace the bulk heterojunction (BHJ) architecture to realize excellent OSCs for certain unique donors and acceptors, giving an alternative approach for photovoltaic material design and device fabrication.